2011
DOI: 10.1021/cb100399x
|View full text |Cite
|
Sign up to set email alerts
|

Identification, in Vitro Activity and Mode of Action of Phosphoinositide-Dependent-1 Kinase Inhibitors as Antifungal Molecules

Abstract: Although protein kinases have recently emerged as important drug targets, the anti-infective potential of protein kinase inhibitors has not been developed extensively. We identified the mammalian PDK1 inhibitor KP-372-1 as a potent antifungal molecule with activity against yeast and fungal biofilms using a screening strategy for protein kinase inhibitors that block the cell wall stress response in yeast. Genetic and biochemical studies indicate that KP-372-1 inhibits fungal PDK1 orthologs (Pkh kinases) as part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 36 publications
(135 reference statements)
2
51
0
Order By: Relevance
“…Furthermore, we show that C. neoformans, like other pathogenic fungi (33)(34)(35), suppresses production of reactive oxygen species (ROS) by mouse macrophage-like J774 cells and that this process is also PKH2-02 dependent. Taken together with our previous work (17), these data indicate that CnPKH2-02-mediated signaling is crucial to C. neoformans stress tolerance and host-pathogen interactions and, consequently, further support the notion that PKHs represent a highly attractive antifungal drug target.…”
supporting
confidence: 86%
See 4 more Smart Citations
“…Furthermore, we show that C. neoformans, like other pathogenic fungi (33)(34)(35), suppresses production of reactive oxygen species (ROS) by mouse macrophage-like J774 cells and that this process is also PKH2-02 dependent. Taken together with our previous work (17), these data indicate that CnPKH2-02-mediated signaling is crucial to C. neoformans stress tolerance and host-pathogen interactions and, consequently, further support the notion that PKHs represent a highly attractive antifungal drug target.…”
supporting
confidence: 86%
“…As mentioned above, one of our laboratories has recently demonstrated that molecules which inhibit hPDK1 also have antifungal activity and appear to target fungal Pkh kinases as part of their mechanism of action (17). Based on the results from Fig.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations